2018
DOI: 10.1002/chem.201800742
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Identification of Aryl and Alkyl Gem‐Dilithium Phosphido‐Boranes: A Boost to the Chemistry of Phosphandiides

Abstract: The synthesis and identification of unprecedented gem-dianionic phosphorus compounds, that is, gem-dilithium phosphido-boranes Li [RP⋅BH ], with R=Ph or Cy, are reported in THF solution. These were obtained by double deprotonation of the corresponding primary phosphine-borane precursors RPH ⋅BH . Their in-depth structural study, based on multinuclear ( H, Li, Li, B, C, P) mono- and bi-dimensional NMR analyses, indicates a strong influence of the phosphorus substituent on the structure of the gem-dianionic phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…During our investigations, [19] Oulyadi, Gaumont, Harrison‐Marchanda et al. reported on the characterization of the gem‐ dilithium phosphido‐borane Li 2 [PhP⋅BH 3 ] intermediate 3 a in THF solution, which matches with our findings, but they did not provide structural characterization in the solid state [20] . We anticipated that the BH 3 moiety might assist the crystallization of this unique dianion and indeed found it to be possible to obtain the highly reactive phosphanediide 3 a as a colorless solid (91 %), which can be recrystallized from a mixture of THF, DME and hexanes at −78 °C to provide colorless crystals suitable for X‐ray analysis.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…During our investigations, [19] Oulyadi, Gaumont, Harrison‐Marchanda et al. reported on the characterization of the gem‐ dilithium phosphido‐borane Li 2 [PhP⋅BH 3 ] intermediate 3 a in THF solution, which matches with our findings, but they did not provide structural characterization in the solid state [20] . We anticipated that the BH 3 moiety might assist the crystallization of this unique dianion and indeed found it to be possible to obtain the highly reactive phosphanediide 3 a as a colorless solid (91 %), which can be recrystallized from a mixture of THF, DME and hexanes at −78 °C to provide colorless crystals suitable for X‐ray analysis.…”
Section: Resultssupporting
confidence: 89%
“…During our investigations, [19] Oulyadi,G aumont, Harrison-Marchanda et al reported on the characterization of the gemdilithiump hosphido-borane Li 2 [PhP•BH 3 ]i ntermediate 3a in THF solution, which matches with our findings, but they did not provides tructural characterization in the solid state. [20] We anticipated that the BH 3 moiety might assist the crystallization of this unique dianion and indeedf ound it to be possible to obtain the highly reactive phosphanediide 3a as ac olorless solid (91 %), which can be recrystallizedf rom am ixture of THF, DME and hexanes at À78 8Ct op rovide colorless crystals suitable for X-ray analysis. The molecular structure of 3a features the dianionic [PhP•BH 3 ]f ragment, of which the phosphorus atom connects to four lithium ions in the polymeric chain in the direction of the crystallographic b-axis (P1ÀLi1 2.550(3), P1ÀLi2 2.524(4), P1ÀLi1 ii 2.540(4), P1ÀLi2 ii 2.561(4) ;F igure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Other organolithium complexes characterised using an internal calibration method include chiral enolate aggregates [173], THF-solvated 1,4-dienolates [174], 2,2,6,6tetramethylpiperidides [175,176], pinacolone enolate [177], aryl and alkyl gem-dilithium phosphido-boranes [178], chiral lithium amides derived from valinol derivatives [179,180], N-isopropyl alaninol [181] and S-valine [182], as well as the identification of hexameric and octameric sec-butyllithium/sec-butoxide mixed aggregates [183]. Such studies are not limited to single metal complexes.…”
Section: Internal Calibration -Examples and Applicationsmentioning
confidence: 99%
“…Since then, a limited number of alkali and alkaline earth metal complexes, [7,8] a very limited number of p‐block complexes, [6,7b,10] and a small number of transition metal complexes of these ligands have been reported [4,5] . A small number of diaminophosphido‐borane complexes [(R 2 N) 2 P(BH 3 )]M have also been isolated, [11] while, very recently, the synthesis of a series of gem ‐dilithium phosphido‐boranes [RP(BH 3 )]Li 2 has been described [12] . In view of the limited previous studies of the coordination chemistry of phosphido‐borane ligands, a systematic study of the impact of the substituents and metal centers on the structures of these compounds appears warranted.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] A small number of diaminophosphido-borane complexes [(R 2 N) 2 P(BH 3 )]M have also been isolated, [11] while, very recently, the synthesis of a series of gem-dilithium phosphido-boranes [RP(BH 3 )]Li 2 has been described. [12] In view of the limited previous studies of the coordination chemistry of phosphido-borane ligands, a systematic study of the impact of the substituents and metal centers on the structures of these compounds appears warranted. In this contribution, we report the synthesis of a series of differently-substituted phosphidoborane complexes of lithium and sodium and show how the structures of these compounds are affected by the nature of the substituents and the alkali metal.…”
Section: Introductionmentioning
confidence: 99%